Correction to: Effects of enriched-potassium diet on cardiorespiratory outcomes in experimental non-ischemic chronic heart failure - Schwarz, Karla G.; Pereyra, Katherin V.; Toledo, Camilo; Andrade, David C.; Díaz, Hugo S.; Díaz–Jara, Esteban; Ortolani, Domiziana; Rios–Gallardo, Angélica; Arias, Paulina; Heras, Alexandra Las; Vera, Ignacio; Ortiz, Fernando C.; et al. (My University, 2022)
Following publication of the original article [1], the Figs. 2, 3 and 4 are misplaced. The correct order of figures is given in this erratum (Figs. 1, 2, 3, 4, 5, 6). The original article has been corrected.